AB1018 CONE BEAM CT IN JUVENILE IDIOPATHIC ARTHRITIS: ROLE OF IMAGING DIAGNOSTIC TOOL WITH MINIMAL X-RAY EXPOSURE IN THE FREQUENT, SUBTLE AND INDOLENT TEMPOROMANDIBULAR JOINT INVOLVEMENT. (June 2019) - Maschio, Maddalena; Pieropan, Sara; Aiello, Giulia; Melotti, Giulia; Tadiotto, Elisa; Giacomelli, Erica; D'agostino, Antonio; Trevisiol, Lorenzo; Piacentini, Giorgio
Abstract : Background: The prevalence of the temporomandibular joint (TMJ) involvement in patients affected by juvenile idiopathic arthritis (JIA) ranges from 17% to 87% depending on population. TMJ is frequently the first and unique joint involved in the arthritic process. Unfortunately detection of TMJ arthritis in children with JIA is difficult as early signs and symptoms are missing in most patients. Therefore failure to diagnose and treat TMJ arthritis may have severe consequences on masticatory function, like pain at biting, chewing and yawning and moreover mandibular growth can be impaired and facial asymmetries may develop. Although Magnetic Resonance Imaging (MRI) is the gold standard to identify TMJ involvement, it is affected by lack of informations about bone components. Cone beam CT (CBCT), an imagine diagnostic tool with minimal xray exposure, thanks to its 3D studies provides an accurate image of anatomical bone alteration. Objectives: Provide a screening imaging tool for TMJ involvement in JIA patients so TMJ dysfunction can be detected and managed at an early stage. Methods: Eighteen patients affected by JIA from 2 to 16 yeas of age were included in this prospective study (M/F, 3/15); they were all admitted to a Pediatric Rheumathology and Maxillofacial Surgery Integrated out-patient ambulatory, where an experienced surgeon focused on evaluation of TMJs. All symptomatic patients (uni or bilateral TMJ's pain) performed MRI: anomalous imaging such as increased joint enhancement or intra-articular effusion, was treated with intra-articular corticosteroid injections (IACI). After about two month from intra-articular treatment CBCT was performed in all the enrolled patients (symptomatic and not). Results: CBCT is a useful tool to improve the diagnostic and therapeutic iter of TMJ involvement in JIA; in fact on one hand it highlights the unsuccessful and palliative role of IACI and on the other hand it can reveal significant impairment of the joint bone components in frequent asymptomatic patients; systemic therapy from the early phase of TMJ involvement could prevents the irreversible modification of the mandibular growth process of undertreated inflammation Conclusion: CBCT is a useful tool to improve the diagnostic and therapeutic iter of TMJ involvement in JIA; in fact on one hand it highlights the unsuccessful and palliative role of IACI and on the other hand it can reveal significant impairment of the joint bone components in frequent asymptomatic patients; systemic therapy from the early phase of TMJ involvement could prevents the irreversible modification of the mandibular growth process of undertreated inflammation. References: [1] Farronato G. et all "Craniofacial Growth in Children Affected by Juvenile Idiopathic Arthritis Involving the Temporomandibular Joint: Functional Therapy Management". The Journal of Clinical Pediatric Dentistry 33(4):351–358, 200 [2] Keller H., et all." Is early TMJ involvement in children with juvenile idiopathic arthritis clinically detectable? Clinical examination of the TMJ in comparison with contrast enhanced MRI in patients with juvenile idiopathic arthritis". Pediatric Rheumatology (2015) 13:56 [3] Silvia Caruso, et all. "Temporomandibular Joint Anatomy Assessed by CBCT Images". BioMed Research International.2017:2916953. Disclosure of Interests: None declared